Legal anomie in the legal system: theoretical and methodological bases of research - A. V. Malko; D. A. Lipinsky; R. S. Markunin (Правоприменение, 2023)
A comprehensive general theoretical analysis of legal anomie in the legal system of modern Russian society is carried out. It is said that the theory of state and law currently lacks even the foundations of a holistic concept of legal anomie, but it is precisely this that acts as one of the causes of corruption, terrorism, extremism, legal irresponsibility, a high level of delinquency, massive non-compliance with prohibitions, distancing a significant number of citizens from state power and its rejection. The authors note that anomie to one degree or another always exists. At the same time, the state of social anomie inevitably increases when significant changes occur that affect the social structure and norms. Anomie is an interdisciplinary category that requires appropriate approaches to itself. Social anomie is based on the general interdisciplinary concept of "social deviations", which is studied by a variety of sciences: philosophy, sociology, psychology and many others. A brief description of the theoretical and methodological foundations of the study of social deviations, social anomie and its specific variety - legal anomie is given. For the most complete analysis of legal anomie, it is proposed to use not only systemic (within the category "legal system"), but also comprehensive (within the category "social and legal life") approaches, as well as a number of other methods (in particular, historical, structural and functional and statistical). Legal anomie manifests itself in the form of a decline in the value of law and order, a discrepancy between the goals of society and the means to achieve them offered by the state, the lack of trust between society and public authorities, sustainable legal nihilism. And if in sociology (and some other sciences) there are different directions and concepts for understanding anomie, then in the theory of state and law, a system of scientific knowledge about legal anomie has not yet been formed. Legal anomie in the legal system should be considered comprehensively, in development and comparison, revealing the contradictions and mutual conditionality of its various characteristics, possible pairing, as well as the positive and negative aspects of the existing contradictions between legal anomie and individual elements of the legal system of society. Due to the fact that legal anomie in modern society (following the social and legal life) develops and becomes more complicated, it is concluded that it is necessary to further study it, which will provide: firstly, its more complete knowledge and prediction of consequences, and secondly, the development of effective preventive measures, and, thirdly, the strengthening of counteraction to it.